2021
DOI: 10.2174/1570159x18666201023154049
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the COMT Val158Met Polymorphism and Antipsychotic Efficacy in Schizophrenia: An Updated Meta-Analysis

Abstract: Background: Catechol-O-methyltransferase (COMT) contributes to the control of synaptic dopamine (DA) transmission by catalyzing DA degradation in the presynaptic space. The COMT Val158Met polymorphism (rs4680) substantially alters enzymatic activity and consequently synaptic DA concentration in the prefrontal cortex and hippocampus. The COMT genotype could, therefore, exert a major influence on antipsychotic treatment response as many of these agents also target dopaminergic transmission. Objective: The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…First, diverse ethnicities as genetic background plays an important role in antipsychotic treatment response. Second, response phenotype is a complicated trait, differences observed in different studies may be related to heterogeneity of definitions or criteria of response phenotype [15,39]. Third, different sample sizes may result in various outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, diverse ethnicities as genetic background plays an important role in antipsychotic treatment response. Second, response phenotype is a complicated trait, differences observed in different studies may be related to heterogeneity of definitions or criteria of response phenotype [15,39]. Third, different sample sizes may result in various outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Rajagopal VM et al observed that patients with COMT Val/Met or Met/ Met genotype who also had DRD4 120-bp allele revealed a significantly better response to clozapine [20]. Additionally, a meta-analysis reported a significantly improved response in Met-allele carrier Asian and Caucasian patients [39]. COMT is a catabolic enzyme with functional connection to dopaminergic transmission, the first target of most antipsychotics [11,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COMT rs4680 variant (Val158Met), associated with reduced cortical dopamine [18], has been associated with response to second-generation antipsychotics [19,20]. A recent meta-analysis confirmed the strength of this association (Z = 6.709, p = 9.8 × 10 −12 ) [21]. Variants of the BDNF gene were associated with risperidone and clozapine response [22] and with treatment resistance [23].…”
Section: Pharmacogenetic Associations With Treatment Responsementioning
confidence: 97%
“…The Met allele is associated with reduced catabolic activity and is linked to greater tonic and reduced phasic striatal dopaminergic transmission [8]. In particular, COMT Val158Met polymorphism modifies enzymatic activity and, consequently, synaptic dopamine concentration in specific brain areas (prefrontal cortex and hippocampus) [9]. A PET study investigating D1 receptor density suggested that the Val allele was associated with lower levels activity of baseline dopamine in the cortex [10], although no associations were observed in a study on cortical D2 receptors [11].…”
Section: Introductionmentioning
confidence: 99%